Modulation of Tropical Cyclone Genesis in the Bay of Bengal by the Central Indian Ocean Mode. Issue 12 (13th June 2020) - Li, Baosheng; Zhou, Lei; Wang, Chunzai; Gao, Cong; Qin, Jianhuang; Meng, Ze
Abstract: Tropical cyclones (TCs) can be modified by various processes in the multiscale weather and climate system. In this study, the TC genesis locations are found to shift northward in the Bay of Bengal (BoB) due to the intraseasonal central Indian Ocean (CIO) mode. During the positive phase of the CIO mode, convection center moves from the equator to the BoB. Correspondingly, over the BoB, the updraft transports moisture to the mid‐troposphere, and the associated convergence and cyclonic vorticity in the lower troposphere are favorable for TC genesis. The diagnoses on eddy kinetic energy budget indicate that the barotropic energy gain from intraseasonal variabilities nourishes TC genesis over the BoB, which is mainly attributable to the horizontal gradient of zonal winds associated with the enhanced low‐level convergence and vorticity during the positive CIO mode. During the negative CIO mode, convection is around the equator. The TC genesis locations shift southward, but the modifications are not significant. The impacts of the CIO mode on TC genesis over the BoB are different from the influences of Madden‐Julian Oscillation. Hence, the results are expected to contribute to a comprehensive understanding of the relations between TCs and intraseasonal variabilities over the Indian Ocean. Key Points: TC genesis locations are shifted northward in the BoB during the positive phase of the CIO mode, and it is different from the impact of MJO During the positive phase of the CIO mode, convection center moves to the northern BoB, and barotropic energy gain from ISVs nourishes TC genesis The shift of TC genesis locations leads to more TC landfalls over the northern BoB